The influence of job burnout and work engagement toward turnover intention among co-assistant doctors (case study: the medical school of airlangga university, surabaya, Indonesia) - Asrie, Putri Zahra Nabila; Pritasari, Adita (Journal of Business and Management, 2020)
Abstract. Despite having a large number of citizens, Indonesia has a relatively low number of doctors compared to other countries in Southeast Asia. Each year, the number of general practitioners keep decreasing despite the increasing number of medical students. There is an indication that there could be a turnover in the medical field. Turnover itself is known to be caused by high burnout and low engagement at work yet the healthcare industry is known to have both high work engagement and high burnout level. The Medical School of Airlangga University has been one of the biggest contributors in terms of numbers for the general practitioner in Indonesia. However, the number of doctors inaugurated have been stagnant despite the increasing number of undergraduate students. It indicates that something may happen in the process in between which is the co-assistant stage. Due to that reason, this research is aimed to find the influence of job burnout and work engagement toward turnover intention among co-assistant doctors. This study found that both job burnout and work engagement have a significant effect on turnover intention. Even so, it turns out that having a high dedication can help reduce turnover intention the most. As a result, it is recommended for the related institution to allow personal development, and create a supportive work environment as well as providing a social spot.Keywords: Job Burnout, Work Engagement, Turnover Intention, Co-Assistant Doctors.